2019
DOI: 10.1038/s41436-019-0457-6
|View full text |Cite|
|
Sign up to set email alerts
|

Population genomic screening of all young adults in a health-care system: a cost-effectiveness analysis

Abstract: PurposeTo consider the impact and cost-effectiveness of offering preventive population genomic screening to all young adults in a single-payer health-care system.MethodsWe modeled screening of 2,688,192 individuals, all adults aged 18–25 years in Australia, for pathogenic variants in BRCA1/BRCA2/MLH1/MSH2 genes, and carrier screening for cystic fibrosis (CF), spinal muscular atrophy (SMA), and fragile X syndrome (FXS), at 71% testing uptake using per-test costs ranging from AUD$200 to $1200 (~USD$140 to $850).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 37 publications
2
57
0
Order By: Relevance
“…Finally, healthy individuals in families with familial LC should undergo such WES tests because they may share the same fragile germline basis as the probands. This echoes a recent study that the population genomic screening of all young adults is extremely cost-effective in disease prevention and enhancing life quality [32]. Our…”
Section: Discussionsupporting
confidence: 83%
“…Finally, healthy individuals in families with familial LC should undergo such WES tests because they may share the same fragile germline basis as the probands. This echoes a recent study that the population genomic screening of all young adults is extremely cost-effective in disease prevention and enhancing life quality [32]. Our…”
Section: Discussionsupporting
confidence: 83%
“…For breast cancer, BRCA screening in the context of high-risk populations has already been shown to be cost-effective in the USA and UK [10,55], and recent evidence has shown screening for hereditary breast and ovarian cancer genes in an unselected population to be costeffective over testing based on clinical or family history criteria [44]. In addition, a recent cost-effectiveness evaluation of early adulthood screening for BRCA1/BRCA2/MLH1/MSH2 with carrier screening for cystic fibrosis, spinal muscular atrophy and fragile X syndrome in the Australian single-payer system found this approach to be highly effective in preventing cancer deaths and highly cost-effective [56]. Polygenic risk-informed cancer screening has also been shown to be cost-effective in breast cancer [11,57], with evaluations in colorectal and prostate cancer underway.…”
Section: Programme/system Principlesmentioning
confidence: 99%
“…Zhanga et al considered the impact and cost-effectiveness of offering preventive population genomic screening for BRCA1/2, MLH1/MSH2 genes, cystic brosis, spinal muscular atrophy and fragile X syndrome to all young adults (18)(19)(20)(21)(22)(23)(24)(25) years) in a single-payer health-care system in Australia, and reported that it would be highly cost-effective, but ethical issues need to be considered [17].…”
Section: Introductionmentioning
confidence: 99%